Proceso de atención de enfermería en paciente adulto mayor con tuberculosis pulmonar. - Guangatal Guangatal, Luz América (2022)
The present work is about the elaboration of a clinical case of a patient diagnosed with pulmonary tuberculosis, in which the main objective is to apply the nursing care process and the different interventions to improve the patient's prognosis, together with the medical interventions. The work is carried out through the follow-up at the 7 de Octubre Health Center, analyzing the clinical history and collecting data from it. In addition, the theoretical framework was elaborated through the search of different bibliographic sources. And as a result of this clinical case after the interventions, the following was obtained: the correct application of the nursing care process; the clinical case was followed up by means of home visits; the improvement of the clinical picture after the interventions was noted. Therefore, this clinical case became a bibliographic review guide for future works related to this topic.